Effect of mono- and dual frequency power ultrasound assisted enzymolysis on the degree of hydrolysis and ACE inhibitory activity of Stevia protein hydrolysates - Gasmalla, Mohammed Abdalbasit A.; Musa, Abubakr; Awad, Faisal N.; Admassu, Habtamu; Ma, Haile (Tropical journal of pharmaceutical research, 2021)
Purpose: To study the effects of ultrasound pretreatment at different frequencies and working modes, including mono frequency ultrasound (MFU) and dual-frequency ultrasound (DFU), on the degree of hydrolysis (DH) and angiotensin-I-converting enzyme (ACE) inhibitory effect of Stevia protein (SP). Methods: Protein from Stevia leaves was extracted by water (50 g suspended in 1000 mL). The hydrolysis of stevia protein extract (SPE) was carried out using alcalase at 5 % enzyme substrate (E/S) ratio. A study was then carried out to investigate its microstructure and morphology using scanning electron microscopy (SEM). Results: The results showed that ultrasound pretreatment did not increase DH of SP significantly (p > 0.05). However, the highest ACE inhibitory activity of stevia protein hydrolysate was obtained at DFU level (20/50 KHz). Overall, ultrasonic frequency mode had a significant influence on ACE inhibitory activity. Conclusion: The frequency selection of ultrasound pretreatment of SP is essential for the preparation of ACE inhibitory peptide.